GCMS Profile, Antioxidant and Cytotoxic Properties of Sida acuta (Burm f.) - Nalini T.J.; Ramesh Babu H.N; Rajeshwari N.; Manjunath K. M (The Bioscan, 2024)
This study was designed to perform with the main purpose of determining the bioactive components of water (aq.) extract from Sida acuta leaves by GC-MS analysis and characterization. In this study identified 9,12,15-octadecatrienoic acid ethyl ester (Z,Z,Z), 4-hydroxy-e-methylacetophenone, 1,3-propanediol,2-(hydroxymethyl)-2-nitro, 9,12,15-octadecatrienoic acid ethyl ester (Z, Z, Z), alpha-tocopherol & beta-D-mannoside, l-(+)-ascorbic acid 2,6-dihexadecanoate, 3-deoxy-d-mannolactone, hexadecanoic acid and 2-hydroxy-1-(hydroxymethyl) ethyl ester as the predominant compounds present in aq. leaf extract Sida acuta by GC-MS analysis and characterization. In conclusion, all parts of Sida acuta is used for therapeutic purposes, but the leaves are most widely used, and therefore further in-vitro and in-vivo research is recommended to evaluate the predominant pharmacological activities compounds identified in aq. Sida acuta leaf extract.